Eksistensi Kertas Berharga Digital dalam Sistem Pembayaran Elektronik - Agustian, Muhamad Yosi (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2025)
Valuable papers such as checks, bilyet giro and promissory notes were originally designed as physical-based payment instruments that have legal force and economic value. However, as people's preference for electronic payment systems (e-payment) increases, questions arise about the sustainability and existence of valuable paper in physical form in this era of digitization. This study uses normative legal research methods. The problem in this writing is the legal position of digital valuable paper in the electronic payment system according to Indonesian positive law and juridical and practical challenges in the implementation of digital valuable paper in Indonesia. In conclusion, digital valuable paper currently does not have a firm legal basis in Indonesia's positive legal system and the implementation of digital valuable paper cannot be done effectively, safely and legally and still poses legal and technological risks to the parties who use it. Suggestion, legal reform is urgently needed through the revision of the criminal code or the preparation of new laws that explicitly recognize and regulate valuable paper in digital form, legal education and digital technology training need to be improved, both for financial industry players, Business actors, and law enforcement officers, so that they are ready to adapt and understand the risks and legal protections in digital-based transactions